UPAYA PENERAPAN KONSEP MUSEUM BARU PADA MUSEUM SATRIA MANDALA JAKARTA - Dhanisa Restya Agung (SANGIA: Jurnal Penelitian Arkeologi, 2024)
The concept of museums by new museums is to be relevant and useful to education and to involve community participation. As for the problem of this research, how to manage the new museum-based concept. The purpose of this study is that the Knight Mandala Museum may go hand in hand with novelty or according to current conditions to serve and address people's needs according to the concept of a new museum. The methods of research used in this study are qualitative using the new museum concept and applying the concept of mutation themes. The collection of data that is done is by using primary and secondary data. Research on the whereabouts of the Knight Mandala Museum will now require an effort on management based on the new museum's concept of education and civic role.